2017
DOI: 10.1037/emo0000204
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and anxiety, social synchrony, and infant regulation of negative and positive emotions.

Abstract: Maternal postpartum depression (PPD) exerts long-term negative effects on infants; yet the mechanisms by which PPD disrupts emotional development are not fully clear. Utilizing an extreme-case design, 971 women reported symptoms of depression and anxiety following childbirth and 215 high and low on depressive symptomatology reported again at 6 months. Of these, mothers diagnosed with major depressive disorder (n = 22), anxiety disorders (n = 19), and controls (n = 59) were visited at 9 months. Mother-infant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(213 citation statements)
references
References 150 publications
(207 reference statements)
8
203
2
Order By: Relevance
“…Previous research has linked child positive affectivity to both positive and negative outcomes, and in their review, Davis and Suveg () suggested that it might moderate the relationships between contextual factors and indices of child adjustment and maladjustment. A link between low levels or a lack of child positive affectivity and an increased risk for later depression has emerged in many studies, particularly in families where parents have depressive disorders (Olino et al., ; Granat, Gadassi, Gilboa‐Schechtman, & Feldman, ). In our study, 29% of the mother–infant dyads did not have SP in the 5‐min time period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has linked child positive affectivity to both positive and negative outcomes, and in their review, Davis and Suveg () suggested that it might moderate the relationships between contextual factors and indices of child adjustment and maladjustment. A link between low levels or a lack of child positive affectivity and an increased risk for later depression has emerged in many studies, particularly in families where parents have depressive disorders (Olino et al., ; Granat, Gadassi, Gilboa‐Schechtman, & Feldman, ). In our study, 29% of the mother–infant dyads did not have SP in the 5‐min time period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies point to disruptions in mother–child synchrony in cases of maternal depression in infancy (Beebe et al., ; Granat et al., ; Weinberg & Tronick, ), but we are aware of no study that measured synchrony in relation to maternal depression beyond infancy. Since synchrony is longitudinally linked with children's externalizing and internalizing problems, it is possible that the experience of synchrony may help to promote resilience in the context of maternal depression.…”
Section: Introductionmentioning
confidence: 86%
“…In cases of insufficient maternal regulation, the optimal developmental trajectory shifts to place infants at risk of psychopathology [56]. It was recently demonstrated that mothers who suffer from post-partum depression are less synchronous with their infants, and such reduced social synchrony disrupts the infant’s emotion regulation *[57]. The authors suggested that compromised regulation of emotion is behaviorally transferred from the depressed mother to her infant.…”
Section: Caregiver Processes Are Critical For Conceptualization and Ementioning
confidence: 99%